From Errors to Probability Density Functions. Evolution of the Concept of Measurement Uncertainty - Bich, W. (IEEE transactions on instrumentation and measurement, 2012)
The concept of uncertainty in measurement stems from that of (probable) error and is intimately intertwined with it. Both concepts can be viewed as measures of the quality of a measurement or, better, of the corresponding estimate. There is an endless list of misunderstandings, false beliefs, and misinterpretations on this subject. People tend also to use the same word with different meanings. In this paper, while giving an overview of the evolution of the concept, from the initial unawareness of the need for a quality assessment (still present in many areas) to the present views, the author also tries to shed some light and some clarity on the most popular and debated misunderstandings, particularly about the concepts of error, true quantity value(s), and measured quantity value. The author is the convener of the Joint Committee for Guides in Metrology Working Group 1 (Guide to the expression of uncertainty in measurement). The opinion expressed in this paper does not necessarily represent the view of this working group.